PENGARUH MODEL PEMBELAJARAN CORE (CONNECTING, ORGANIZING, REFLECTING, EXTENDING) TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS - Hermawan, Vevi; Fauzi Azis Pratama; Taufik Rahman (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2024)
The ability to think mathematically critically in learning mathematics is essential for students to understand and help solve a problem in math. The ability to think critically mathematically is very low. One of the learning alternatives that can be used in training mathematical critical thinking skills is through the CORE learning model. (Connecting, Organizing, Reflecting, Extending). The study aims to find out whether the influence of students' ability to think mathematically critically has been achieved on the higher CORE learning model among students who obtained expository learning. The method used in this research is semu experiment (quasi experiment) with non-equivalent control group design, the subject of this study is a student of class XI High School Pasundan 3 Bandung. Sampling techniques use purposive sampling, using two classes: experimental class and control class.